2016
DOI: 10.1002/mnfr.201500827
|View full text |Cite
|
Sign up to set email alerts
|

Urolithin A attenuates ox‐LDL‐induced endothelial dysfunction partly by modulating microRNA‐27 and ERK/PPAR‐γ pathway

Abstract: UA could alleviate endothelial dysfunction induced by ox-LDL partially through modulating miR-27 expression and ERK/PPAR-γ pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 58 publications
4
38
0
Order By: Relevance
“…In this context, we recently showed that urolithins are able to reduce the pro-inflammatory response to high glucose levels in cultured neonatal cardiomyocytes and fibroblasts [13], suggesting that they can prevent the diabetes-induced microenvironmental changes triggering myocardial inflammation and functional impairment in the diabetic heart. These findings confirmed previous in vitro studies demonstrating the positive role of urolithin supplementation in different cell models, including anti-inflammatory activity in endothelial cells and macrophages [15, 3236] and beneficial effects on lipid metabolism in adipocytes and hepatocytes [37]. However, the biological effects of in vivo urolithin administration in the setting of diabetes, as well as in other pathological conditions, remain to be characterized [38].…”
Section: Discussionsupporting
confidence: 87%
“…In this context, we recently showed that urolithins are able to reduce the pro-inflammatory response to high glucose levels in cultured neonatal cardiomyocytes and fibroblasts [13], suggesting that they can prevent the diabetes-induced microenvironmental changes triggering myocardial inflammation and functional impairment in the diabetic heart. These findings confirmed previous in vitro studies demonstrating the positive role of urolithin supplementation in different cell models, including anti-inflammatory activity in endothelial cells and macrophages [15, 3236] and beneficial effects on lipid metabolism in adipocytes and hepatocytes [37]. However, the biological effects of in vivo urolithin administration in the setting of diabetes, as well as in other pathological conditions, remain to be characterized [38].…”
Section: Discussionsupporting
confidence: 87%
“…The decreased PPAR-γ is a critical determinant for ox-LDL-induced endothelial dysfunction [24]. Endothelial PPAR-γ is recognized as a potential candidate for vascular protection from atherosclerosis [25].…”
Section: Resultsmentioning
confidence: 99%
“…The therapeutic effect of urolithin has been widely recognized (36)(37)(38)(39)(40). Urolithin can enhance the anti-inflammatory effects of neutrophils, alleviate the symptoms of inflammation (36) and protect against prostate cancer (37).…”
Section: Discussionmentioning
confidence: 99%
“…Uro-A and uro-B increase cell viability and protect cells, reduce malondialdehyde content and enhance superoxide dismutase activity (38). Uro-A regulates the expression of intercellular adhesion factor-1 via the ERK/peroxisome proliferator activated receptor-γ signaling pathway, which exerts anti-inflammatory effects (39). Uro-A also induces mitophagy, prolongs the lifespan of Caenorhabditis elegans and increases muscle function in rodents (40,41).…”
Section: Discussionmentioning
confidence: 99%